Insulin degludec is a new ultra-long-acting insulin analogue - Ivan Ivanovich Dedov; Marina Vladimirovna Shestakova (Сахарный диабет, 2014)
Achieving optimal glycemic control is an important aspect of preventing and slowing the progression of diabetes-associated complications, and reducing the cost of their treatment. Long-acting insulin analogues, glargine and detemir, provide better metabolic control with reduced risk of hypoglycaemia as compared to NPH insulin. However, fear of hypoglycaemia and weight gain, as well as the complexity of regimen, are still the most important barriers to well-timed initiation and intensification of insulin therapy. Insulin degludec (Tresiba?) is a new ultra-long-acting insulin analogue. After subcutaneous injection degludec forms repository of soluble multi-hexamers, which are gradually absorbed to the bloodstream, providing a flat, stable antihyperglycemic effect lasting more than 42 h, and low intra-individual variability as opposed to currently used basal insulin analogues, insulin glargine and insulin detemir. In the seven randomized, open label, controlled phase 3 trials lasting 26 or 52 weeks, using treat-to-target (no more) non-inferiority design, insulin degludec provided glycemic control similar to that of insulin glargine with lower risk of nocturnal hypoglycaemia and good safety profile in patients with type 1 or 2 diabetes. Furthermore, trials examining a flexible dosing regimen of insulin degludec in patients with type 1 or 2 diabetes have shown that it is possible to vary the injection time without compromising glycemic control or safety of the therapy.